Knowledge, Perception, Attitude and Social Culture as Determinant of Male Participation in Family Planning - Surya Dewi Puspita; Sri Hernawati; Farida Wahyu Ningtyias (Humanistic Network for Science and Technology (HNST), 2018)
Family Planning Program (KB) aims to improve women status and reducing population growth for the achievement of family welfare by limiting pregnancy by using contraception.. Family planning programs in Indonesia are still dominated by women and in Jember Regency the contraceptive acceptors are almost entirely female. The purpose of this study was to analyze the influence of knowledge, attitudes, perceptions and social culture on the male participation of fertile-age in family planning program. The type of this research is analytic observational with cross sectional research design. Data were collected from 380 male fertile-age using contraception and not using contraception. Sampling technique in this research used multistage random sampling technique. The results of the study used logistic regression test showed that the level of knowledge influenced the male participation of fertile-age in family planning program (p = 0.000), perception influenced the male participation of fertile-age in family planning program (p = 0.000) attitude influenced the male participation of fertile-age in family planning program (p = 0.000), socio-cultural influence the male participation of fertile-age in family planning program (p = 0.003). Keywords: Male, Knowledge, Perception, Attitude, Socio-culture, Family planning